2004
DOI: 10.1002/cncr.20256
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the ovary

Abstract: BACKGROUNDA review of clinicopathologic features and outcome in women with carcinosarcoma of the ovary (also known as malignant mixed mesodermal tumor [MMMT]) compared with a group of women with serous adenocarcinoma (SAC) of the ovary was conducted.METHODSBetween 1984 and 2002, 1568 patients with epithelial ovarian carcinoma and 70 patients with ovarian carcinosarcoma underwent treatment at the Edinburgh Cancer Centre. Analysis was performed on 65 patients with MMMT, and 746 patients with SAC were selected as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
4
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 20 publications
(31 reference statements)
3
44
4
10
Order By: Relevance
“…Due to the small number in our study, the majority of patients (12) were stage IIIC and 1 stage IVB and all were older with an average age of 65 years. Similarly to the results reported by Brown et al and Muntz et al [3,11], and in contrast to those published by Barakat et al [12], our study found a trend toward improved survival after optimal debulking, with a median survival of 30 months in patients who were optimally debulked compared to a median survival of 5 months in patients who were suboptimally debulked.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Due to the small number in our study, the majority of patients (12) were stage IIIC and 1 stage IVB and all were older with an average age of 65 years. Similarly to the results reported by Brown et al and Muntz et al [3,11], and in contrast to those published by Barakat et al [12], our study found a trend toward improved survival after optimal debulking, with a median survival of 30 months in patients who were optimally debulked compared to a median survival of 5 months in patients who were suboptimally debulked.…”
Section: Discussioncontrasting
confidence: 57%
“…12 were stage IIIC and 1 stage IVB. In contrast to Brown et al [3], it is interesting to note that in our study the positivity of CA-125 at diagnosis was present in 10 cases and it was not correlated with a poor prognosis. This was probably due to the small number of our series.…”
Section: Discussioncontrasting
confidence: 54%
“…Owing to the rarity of ovarian carcinosarcomas, there is no established chemotherapy regimen [2] . Lesier et al have evaluated the combination of platinum and taxane either after initial tumor resection or as neoadjuvant therapy [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian carcinosarcoma, also known as malignant mixed Müllerian or mesodermal tumor (MMMT), is uncommon accounting for approximately 1% to 2% of all ovarian malignancies [1,2] . In the female genital tract, carcinosarcomas usually arise in the uterus and much less frequently in the ovary, vagina and cervix, with a tendency to affect the elderly population [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation